BUTYRATE AMELIORATES PANETH CELL DEFECTS, TOTAL INFLAMMATION, AND EPITHELIAL CELL APOPTOSIS DURING MITOCHONDRIAL DYSFUNCTION DRIVEN BY PROHIBITIN 1-DEFICIENCY. (26th January 2023) - Alula, Kibrom; Dowdell, Alexander; Lee, Joseph; Colgan, Sean; Theiss, Arianne
Abstract: INTRODUCTION: Prohibitin 1 (PHB1) is a mitochondrial chaperone protein important for maximal activity of the electron transport chain. PHB1 deficiency in intestinal epithelial cells (IECs) or specifically in Paneth cells (PCs) induces epithelial mitochondrial dysfunction, PC defects, gut microbiota dysbiosis, and spontaneous ileitis in mice by 20 weeks-of-age. Dysbiotic gut microbiota has been implicated in inflammatory bowel diseases and is associated with the decreased abundance of short chain fatty acids (SCFAs; acetate, propionate, and butyrate)-producing bacteria. SCFAs play a significant role in reducing intestinal inflammation and epithelial barrier dysfunction. We tested the hypothesis that luminal SCFA levels were decreased in mice with PHB1 deficiency and that supplementation of SCFAs will ameliorate intestinal inflammation during mitochondrial dysfunction driven by loss of PHB1. METHODS: Ileal luminal contents were collected from Phb1 fl/fl (control) and Phb1 iΔIEC ( Phb1 -deficient in IECs) mice at 20 weeks of age and SCFAs were measured by gas chromatography-mass spectrometry. Phb1 iΔIEC and Phb1 fl/fl littermate mice were treated with 20 mM butyrate dissolved in their drinking water from 16 to 20 weeks-of-age and PC defects were measured by antimicrobial peptide expression (Lysozyme, Cryptdin 3, Cryptdin 5, and Ang4) and Lysozyme staining allocation into secretory granules. Ileitis was measured by histological scoring and pro-inflammatory cytokine expression. To test epithelial intrinsic responses, ileal crypt enteroids derived from Phb1 iΔIEC and Phb1 fl/fl littermate mice were treated with 200 µg/ml healthy ileal stool lysates (from Phb1 fl/fl mice) or dysbiotic stool lysates (from Phb1 iΔIEC mice) for 16 hours with or without 0.05 mM butyrate, 0.5 mM propionate, 0.5 mM acetate, alone or in combination. Enteroid viability and apoptosis were measured by morphological change and cleaved Caspase 3 expression. RESULTS: Butyrate was significantly decreased in ileal stool of Phb1 iΔIEC mice. Butyrate supplementation in Phb1 iΔIEC mice protected against ileitis and PC defects. Dysbiotic stool lysate decreased viability and increased apoptosis in Phb1-deficient enteroids that were prevented by butyrate supplementation. CONCLUSION: Mitochondrial health in IECs cells is crucial for healthy gut microbiota composition and for epithelial defense when the microbiome becomes dysbiotic. Butyrate rescues IECs from insults caused by dysbiotic gut microbiota during mitochondrial dysfunction driven by PHB1 deletion.